PELATIHAN REPARASI HANDPHONE BAGI SISWA SMK 5 DI KOTA LHOKSEUMAWE - Syahrul Azmi; Hanafi Hanafi; Zulkifli Zulkifli; Indra Wijaya (Jurnal Pengabdian Kepada Masyarakat, 2022)
Currently the use of mobile phones (HP) is not only in the field of communication but extends to various online transactions. Not only that, but during a pandemic, the learning process and seminars are conducted online. Utilization of HP is not only from certain circles or ages, but almost all groups and ages, both adults and children, use HP for business and entertainment. Webinars and online are one of the important strategies to fill school activities that were stopped during the pandemic. Over time and during the pandemic, the use of HP increased sharply. It is common nowadays that we see every opportunity and in various places people spend their time with HP. This of course will result in HP being damaged or error quickly. Seeing this condition, it is important for SMK students to have the expertise to repair cellphones that are damaged or have errors. Repairing a cellphone must first understand the theory of the device both hardware and software. Hardware-wise, the first step is how to open the HP case itself and use a precise toolkit, recognize the electronic components contained inside, map out potential damage that occurs and finally replace damaged components or modules. In software, what is done is to find the cause of the operating system or application program that is corrupt or degraded. Is it necessary to take action to upgrade or update the application software? For that students need basic training on how to repair HP. Sometimes everyone who has a damaged cellphone immediately takes it to a technician, and the price is very expensive even though the level of damage is very simple. If you understand the symptoms of damage and understand the basics of electronics, the HP damage can be repaired.